2010
DOI: 10.1111/j.1360-0443.2010.03050.x
|View full text |Cite
|
Sign up to set email alerts
|

Losses disguised as wins in modern multi‐line video slot machines

Abstract: For novice players, the reinforcing sights and sounds of the slot machine triggered arousal on wins, where the number of credits gained was greater than the spin wager, but also on 'losses disguised as wins' where the amount 'won' was less than the spin wager. Despite the fact that players lost money on these spins, these outcomes were more arousing than regular losses where no credits were gained. Although these findings involve novice players, the heightened arousal associated with these losses may have impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
137
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(154 citation statements)
references
References 10 publications
10
137
1
Order By: Relevance
“…Thus, despite being net losses, and making no difference to the overall rate of payout, the occurrence of LDWs acted to increase the trial-by-trial enjoyment of the game. Previous studies have indicated that LDWs induce elevated skin conductance responses compared to other non-win outcomes, related to the sensory feedback associated with winning (Dixon et al, 2010). Our results extend this work to show elevated valence responses to trials with LDWs, such that the presence of LDWs increases the enjoyment of non-win outcomes.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Thus, despite being net losses, and making no difference to the overall rate of payout, the occurrence of LDWs acted to increase the trial-by-trial enjoyment of the game. Previous studies have indicated that LDWs induce elevated skin conductance responses compared to other non-win outcomes, related to the sensory feedback associated with winning (Dixon et al, 2010). Our results extend this work to show elevated valence responses to trials with LDWs, such that the presence of LDWs increases the enjoyment of non-win outcomes.…”
Section: Discussionsupporting
confidence: 78%
“…The LDW response is similar in magnitude to the response to actual wins (Dixon, Harrigan, Sandhu, Collins, & Fugelsang, 2010) and also generates a 'post reinforcement pause', which is seen as a consummatory response to reward . In a notable study, Jensen et al (2013) found that LDWs were verbally miscategorized as wins, and that players' estimates of the number of wins after the game were higher when they were exposed to more LDWs.…”
Section: Introductionmentioning
confidence: 91%
“…However, in some cases, the size of the win can be less than the spin's wager resulting in a net loss rather than a net win for that spin. This outcome is denoted as 'losses disguised as wins' (LDWs; Dixon, Harrigan, Sandhu, Collins, & Fugelsang, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Data obtained from the gambling industry for the purposes of this inquiry revealed that 82-85 percent of gamblers bet at or below one dollar per spin, with an average of 64 cents, and that most gamblers selected a minimum bet with maximum lines as found in previous studies (Dixon et al 2010;Livingstone et al 2008;Productivity Commission 2010). Around 37 percent of revenue was derived from bets above one dollar per spin.…”
Section: Reduction Of Maximum Betsmentioning
confidence: 80%